“Vida em Abundância” e “Saúde para Todos”: Igreja e movimentos sociais pela saúde na década de 1980 (“Life in Abundance” and ‘Health for All”: Church and social movements for health in the decade 1980) - DOI: 10.5752/P.2237-8871.2014v15n22p135 - Machado, Marilane (Cadernos de História, 2014)
<!--[if gte mso 9]> <![endif]-->Neste artigo, discute-se a aproximação entre Igreja Católica e Movimentos Sociais pela Saúde nos anos 1980 a partir do estudo da relação da Pastoral da Saúde com o Centro Brasileiro de Estudos em Saúde de Florianópolis, Santa Catarina. Ambos os grupos fizeram parte do Movimento de Reforma Sanitária de Santa Catarina. Essa aproximação é demonstrada pela análise de cartilhas elaboradas pelos dois movimentos na ocasião da Campanha da Fraternidade de 1981; do Manual da Pastoral da Saúde, elaborado em 1987, com o objetivo de treinar agentes de pastoral no período e; de relatórios da Pastoral da Saúde. Abstract This article seeks to discuss the approach between Catholic Church and Social Movements for Health in 1980s from the particular case of the relationship amid the Ministry of Health and the Brazilian Center for Health Studies in Florianópolis, Santa Catarina. Both groups, from their actions, were part of the Health Reform Movement in Santa Catarina. This rapprochement is demonstrated through analysis of materials prepared by the two movements during the Fraternity Campaign 1981. Also, the Manual of Health Pastoral Care was analyzed. It was developed in 1987 with the aim of training pastoral workers in that period and Health Ministry reports. Keywords: Catholic Church; Social Movements; Public Health; Religions and religiosities; Redemocratization. <!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; mso-bidi-font-family:"Times New Roman";} --> <!--[endif] --><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} -->